Perbedaan Penyerapan Pb pada Berbagai Jenis Tanaman - Sucia Elsa Azzahri; Burhan Muslim; Muchsin Riviwanto (Jurnal Sehat Mandiri, 2020)
Air pollution comes from many factors, one of which comes from vehicles where the smoke produced by motor vehicles contains dangerous heavy metals, Pb. Ujung Gurun Road is one of the densely populated roads which has many pollutant-absorbing plants that line the roadside. This research was conducted with the aim to determine differences in plant types in absorbing lead content (Pb) of air on the road. Analytical research with a comparative study approach. The measurement used is the Wet Ashing Method (wet ashing) for the destruction of the sample, then analyzed using the Atomic Absorption Spectrophotometer (AAS). Data were analyzed using Anova test to see whether there were differences in Glondokan, Mahogany and Angsana plants in absorbing lead air. The results showed lead levels in leaves of glondokan plants were 0.9134 μg / g higher than leaves of mahogany plants as much as 0.764 ug / g and angsana 0.40 ug / g. There is a significant difference in the types of plants in the absorption of air Pb levels in Jalan Ujung Gurun Padang City with p value 0.002 where p <a. For this reason, the monday plant can be used as one of the plants that can be used as one of the government program plants for the absorption of Pb content of air produced by motor vehicles other than mahogany and angsana.